Chemical Composition and Antioxidant Activity of Seed oil of Two Algerian Date Palm Cultivars (Phoenix dactylifera) - Yousfi, Mohamed; Boukouada, Mustapha; Ghiaba, Zineb; Gourine, Nadhir; Bombarda, Isabelle; Saidi, Mokhtar (Natural product communications, 2014)
The fatty acid composition of date seed oil from two different date palm (Phoenix dactylifera L.) cultivars, locally known as Degla-Baïdha and Tafezouine, were investigated. GC analysis revealed the presence of five dominant fatty acids: oleic C18:1 (46.51; 39.15%), lauric C12:0 (22.1; 28.5%), myristic C14:0 (10.7; 11.4%), palmitic C16:0 (9.6; 8.7%) and linoleic C18:2 (6.9; 6.1%). The oils was characterised by a low content of tocopherols (0.53; 1.41 μg/g). The antioxidant activity of the oils was investigated using the DPPH•(1,1-di-phenyl-2-picryl-hydrazyl) scavenging assay. The oils had a weak bleaching effect on DPPH• free radicals. This study showed that the qualities of the tested oils are highly comparable with those of some commercial seed oils of other plants. Furthermore, a statistical analysis using the hierarchy ascendant classification method was conducted in order to highlight the similarities and/or the differences regarding the contents of the main fatty acids found in some common plants and in the five most famous cultivars of Phoenix dactylifera of south eastern Algeria (Tafezouine, Degla-Baïdha, Deglet-Nour, Ghars, Tamdjouhert).
Keywords: Date seeds; Oil; Fatty acids; Phenolic content; Tocopherols; DPPH assay; Hierarchy ascendant classification (HAC).